The novel adipokine CTRP1 is significantly associated with the incidence of major adverse cardiovascular events. (July 2019) - Muendlein, Axel; Leiherer, Andreas; Saely, Christoph; Ebner, Janine; Geiger, Kathrin; Brandtner, Eva Maria; Vonbank, Alexander; Fraunberger, Peter; Drexel, Heinz
Abstract: Background and aims: The recently identified adiponectin paralogue C1q and tumor necrosis factor-related protein 1 (CTRP1) has been associated with obesity-linked disorders and coronary atherosclerosis. So far, the impact of circulating CTRP1 on the incidence of future cardiovascular events is unclear. Therefore, we aimed at investigating the association between CTRP1 and future cardiovascular risk. Methods: We measured CTRP1 serum levels in 539 patients undergoing coronary angiography for the evaluation of established or suspected stable coronary artery disease (CAD). Prospectively, we recorded major adverse cardiovascular events (MACE), defined as the incidence of cardiovascular death, non-fatal myocardial infarction and non-fatal stroke over a follow-up period of 8 years. Results: At baseline, obesity, the metabolic syndrome, type 2 diabetes, and non-alcoholic fatty liver disease were significantly associated with increased CTRP1 (all p -values ≤0.001). Prospectively, MACE rates were lowest in the first quartile (15.3%) and increased over the second (23.7%) to the third and fourth quartile (each 29.0%; p trend = 0.008). Moreover, after multivariable adjustment, CTRP1 was significantly associated with future MACE, with adjusted HRs of 1.83 [1.04–3.23]; p= 0.037, 2.16 [1.25–3.75]; p= 0.006, and 1.80 [1.03–3.15]; p= 0.038, for CTRP1 quartiles two, three and four, respectively, when compared to quartile one. Conclusions: We conclude that high serum levels of CTRP1 are significantly associated with future MACE. Graphical abstract: Image 1 Highlights: CTRP1 is associated with obesity-linked disorders. CTRP1 is associated with future major adverse cardiovascular events. CTRP1 is associated with cardiovascular risk beyond its association with obesity-linked disorders.